NAD(P)H-hydrate dehydratase- a metabolic repair enzyme and its role in Bacillus subtilis stress adaptation - Petrovova, Miroslava; Tkadlec, Jan; Dvoracek, Lukas; Streitova, Eliska; Licha, Irena (PLoS One, 2014)
BACKGROUND: One of the strategies for survival stress conditions in bacteria is a regulatory adaptive system called general stress response (GSR), which is dependent on the SigB transcription factor in Bacillus sp. The GSR is one of the largest regulon in Bacillus sp., including about 100 genes; however, most of the genes that show changes in expression during various stresses have not yet been characterized or assigned a biochemical function for the encoded proteins. Previously, we characterized the Bacillus subtilis168 osmosensitive mutant, defective in the yxkO gene (encoding a putative ribokinase), which was recently assigned in vitro as an ADP/ATP-dependent NAD(P)H-hydrate dehydratase and was demonstrated to belong to the SigB operon. METHODS AND RESULTS: We show the impact of YxkO on the activity of SigB-dependent Pctc promoter and adaptation to osmotic and ethanol stress and potassium limitation respectively. Using a 2DE approach, we compare the proteomes of WT and mutant strains grown under conditions of osmotic and ethanol stress. Both stresses led to changes in the protein level of enzymes that are involved in motility (flagellin), citrate cycle (isocitrate dehydrogenase, malate dehydrogenase), glycolysis (phosphoglycerate kinase), and decomposition of Amadori products (fructosamine-6-phosphate deglycase). Glutamine synthetase revealed a different pattern after osmotic stress. The patterns of enzymes for branched amino acid metabolism and cell wall synthesis (L-alanine dehydrogenase, aspartate-semialdehyde dehydrogenase, ketol-acid reductoisomerase) were altered after ethanol stress. CONCLUSION: We performed the first characterization of a Bacillus subtilis168 knock-out mutant in the yxkO gene that encodes a metabolite repair enzyme. We show that such enzymes could play a significant role in the survival of stressed cells.
Keywords: reduktoizomeráza pro obousměrnou transformaci ketokyselin; reakce na tepelný šok; Bacillus subtilis; glutaminsynthetasa; Ketol-Acid Reductoisomerase; Bacterial Proteins; fosfotransferasy s alkoholovou skupinou jako akceptorem; Adaptation, Physiological; operon; aspartát-semialdehyddehydrogenasa; alanindehydrogenasa; Escherichia coli; regulace genové exprese u bakterií; fyziologická adaptace; fosfoglycerátkinasa; Gene Deletion; Phosphotransferases (Alcohol Group Acceptor); isocitrátdehydrogenasa; osmolární koncentrace; Isocitrate Dehydrogenase; Aspartate-Semialdehyde Dehydrogenase; Phosphoglycerate Kinase; Flagellin; Heat-Shock Response; flagelin; Malate Dehydrogenase; ethanol; Ethanol; Osmolar Concentration; bakteriální proteiny; delece genu; Glutamate-Ammonia Ligase; malátdehydrogenasa; Alanine Dehydrogenase; Gene Expression Regulation, Bacterial; Operon